Testing individual baroreflex responses to hypoxia-induced peripheral chemoreflex stimulation - Kronsbein, Hendrik (Clin Auton Res, 2020)
INTRODUCTION: Baroreflexes and peripheral chemoreflexes control efferent autonomic activity making these reflexes treatment targets for arterial hypertension. The literature on their interaction is controversial, with suggestions that their individual and collective influence on blood pressure and heart rate regulation is variable. Therefore, we applied a study design that allows the elucidation of individual baroreflex–chemoreflex interactions. METHODS: We studied nine healthy young men who breathed either normal air (normoxia) or an air–nitrogen–carbon dioxide mixture with decreased oxygen content (hypoxia) for 90 min, with randomization to condition, followed by a 30-min recovery period and then exposure to the other condition for 90 min. Multiple intravenous phenylephrine bolus doses were applied per condition to determine phenylephrine pressor sensitivity as an estimate of baroreflex blood pressure buffering and cardiovagal baroreflex sensitivity (BRS). RESULTS: Hypoxia reduced arterial oxygen saturation from 98.1 ± 0.4 to 81.0 ± 0.4% (p < 0.001), raised heart rate from 62.9 ± 2.1 to 76.0 ± 3.6 bpm (p < 0.001), but did not change systolic blood pressure (p = 0.182). Of the nine subjects, six had significantly lower BRS in hypoxia (p < 0.05), two showed a significantly decreased pressor response, and three showed a significantly increased pressor response to phenylephrine in hypoxia, likely through reduced baroreflex buffering (p < 0.05). On average, hypoxia decreased BRS by 6.4 ± 0.9 ms/mmHg (19.9 ± 2.0 vs. 14.12 ± 1.6 ms/mmHg; p < 0.001) but did not change the phenylephrine pressor response (p = 0.878). CONCLUSION: We applied an approach to assess individual baroreflex–chemoreflex interactions in human subjects. A subgroup exhibited significant impairments in baroreflex blood pressure buffering and BRS with peripheral chemoreflex activation. The methodology may have utility in elucidating individual pathophysiology and in targeting treatments modulating baroreflex or chemoreflex function.